Effect of age and type of testosterone treatment on cows used for heat detection - G.N. Laaser; G.H. Kiracofe; M.D. Heekin; H.S. Ward; Kenneth G. Odde (Kansas Agricultural Experiment Station Research Reports, 1978)
Twelve cows were given a preliminary treatment of testosterone proprionate and were used to help us detect other cows in heat. We used two types of testosterone booster treatments to maintain male sex behavior in both age groups of cows. Two cows from each treatment or age group were paired and placed with 40 or 60 cows for 30 to 50 days. Two hundred forty-nine cows were observed in heat and 240 (96.4%) were marked by the detector cows. In this experiment, testosterone proprionate boosters maintained cows as heat detectors more effectively than testosterone enanthate boosters.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Testosterone; Heat detection; Proprionate